Carbon capture, utilization, and storage in Indonesia: An update on storage capacity, current status, economic viability, and policy - Romal Ramadhan; Min Thura Mon; Suparit Tangparitkul; Roengchai Tansuchat; Dita Audina Agustin (Energy Geoscience)
As part of its climate action policy, Indonesia prioritizes the development of carbon capture, utilization, and storage (CCUS) facilities. Recognizing the necessity of reducing emissions, Indonesia is aggressively implementing novel carbon capture and storage (CCS) technology. This paper gives a detailed assessment of Indonesia's CCS potential, covering CO2 emission profiles, storage capabilities, active projects, economic feasibility, and policy frameworks. Indonesia plans to cut carbon emissions by 29% by 2030 and reach net zero emissions by 2050. With 15 CCUS projects set to begin by 2026, the government is making tremendous progress toward its targets. The concept includes pilot projects, feasibility studies, and phased adoption of CCUS using existing oil and gas infrastructure. Initiatives such as Tangguh CO2-EGR and Gundih CCS show how smaller-scale projects may pave the way for larger ones. Economic cost assessments show that natural gas processing plants producing high-purity CO2 are the most cost-effective for CCUS. Regulatory developments, such as MEMR February 2023 and Presidential Order No.14/2024, highlight the importance of supporting policies in promoting local and international collaboration. Despite advances, there are still gaps in long-term performance data, risk assessments, and economic consequences for industries such as iron, steel, cement, and chemicals. Future studies should fill these gaps by concentrating on environmental implications, economic viability across several industries, legal and financial obligations, integration with renewable energy sources, and socioeconomic repercussions. Collaborative efforts among government, business, and academia will be critical for the effective development and deployment of CCUS technology following Indonesia's climate goals.